If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 3(5x + -7x) = 12x + -1x Combine like terms: 5x + -7x = -2x 3x + 3(-2x) = 12x + -1x Remove parenthesis around (-2x) 3x + 3 * -2x = 12x + -1x Multiply 3 * -2 3x + -6x = 12x + -1x Combine like terms: 3x + -6x = -3x -3x = 12x + -1x Combine like terms: 12x + -1x = 11x -3x = 11x Solving -3x = 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. -3x + -11x = 11x + -11x Combine like terms: -3x + -11x = -14x -14x = 11x + -11x Combine like terms: 11x + -11x = 0 -14x = 0 Divide each side by '-14'. x = 0 Simplifying x = 0
| 9x-2=7x-8 | | (3x+7)(2x-1)=0 | | 7p-3=2p+2 | | 5x-7x+24=5x+38 | | 7x+3x-6x=5+7 | | 5b-0.5=6b | | 2(x+5)=3(x-1) | | 117=-39k | | 13t=-182 | | 125=-5z | | -3x+8y=48 | | 29t=-145 | | h-11=12 | | 17c=-68 | | 7h=-21 | | 2x(x+5)=20 | | x^2-x-35.74=0 | | x+3/4=2x/3[+2] | | 12=6x^2-4x+4 | | 4n-5(n-2)=5n-14 | | x+3/4=2x/3+2 | | x+3/4=2x/3++2 | | 2y-7=10-7y | | 5-y=2 | | 0-y=2 | | 4(9+6x)=48 | | x-0=2 | | 2x+x+12=0 | | 7.3x-1.7=5.6 | | 14=-3(24-m)+2(m-2) | | 3x+10x=52 | | 29=7y-16x |